2011
DOI: 10.1038/nature10558
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical inflammasome activation targets caspase-11

Abstract: Caspase-1 activation by inflammasome scaffolds comprised of intracellular nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) and the adaptor ASC is believed to be essential for production of the pro-inflammatory cytokines interleukin (IL)-1β and IL-18 during the innate immune response. Here we show, with C57BL/6 Casp11 gene-targeted mice, that caspase-11 (also known as caspase-4) is critical for caspase-1 activation and IL-1β production in macrophages infected with Escherichia coli, Citrobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

99
2,548
9
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,176 publications
(2,680 citation statements)
references
References 35 publications
99
2,548
9
24
Order By: Relevance
“…Recognition of intracellular B. cenocepacia in murine macrophages is mediated through NOD-like receptors including NLRP3 and MEFV/PYRIN [19,20]. Non-canonical NLRP3-PYCARD/ASC-dependent inflammasome activation in response to Gram-negative pathogens requires CASP4 [15]. Here, we report that both CASP4 and MEFV/PYRIN are required for B. cenocepacia -induced CASP1 activation.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Recognition of intracellular B. cenocepacia in murine macrophages is mediated through NOD-like receptors including NLRP3 and MEFV/PYRIN [19,20]. Non-canonical NLRP3-PYCARD/ASC-dependent inflammasome activation in response to Gram-negative pathogens requires CASP4 [15]. Here, we report that both CASP4 and MEFV/PYRIN are required for B. cenocepacia -induced CASP1 activation.…”
Section: Discussionmentioning
confidence: 87%
“…S1B-C) and a 6-fold increase at 6 h compared to non-infected control cells (Figure 1e and g). Because CASP4 stimulates non-canonical NLRP3 inflammasome activation in response to Gram-negative bacteria [15], we further analyzed if CASP4 contributes to B. cenocepacia -induced CASP1 activation. The processing of CASP1 in WT and casp4 −/- macrophages was compared via immunoblot.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial work has identified the pro‐inflammatory cytokine interleukin (IL)‐1β as a key substrate of caspase‐1 (Thornberry et al , 1992). Subsequently, it was found that caspase‐1, as well as caspase‐11 and its human orthologs caspase‐4 and caspase‐5, induces a novel programmed cell death pathway that is characterized by cell swelling, lysis, and the release of cytoplasmic content (Fink & Cookson, 2007; Kayagaki et al , 2011; Shi et al , 2014), presumably as a result of the formation of membrane pores (Fink et al , 2008). Since this type of cell death is morphologically distinct from apoptosis and intrinsically pro‐inflammatory, it was named pyroptosis, from the Greek pyro (fire or fever) and ptosis (to fall) (Bergsbaken et al , 2009).…”
Section: Introductionmentioning
confidence: 99%